2001
DOI: 10.1038/modpathol.3880439
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Telomerase Catalytic Subunit (hTERT) mRNA Does Not Predict Survival in Patients with Transitional Cell Carcinoma of the Upper Urinary Tract

Abstract: Telomerase is a ribonucleoprotein enzyme that synthesizes telomeric repeats onto chromosomal ends using a segment of its RNA component as a template. Its activity has become an established indicator of the diagnosis, biological behavior, and prognosis of several tumors. However, few studies have investigated the diagnostic and prognostic importance of the expression of telomerase catalytic subunit (hTERT) mRNA in transitional cell carcinoma of the upper urinary tract (TCC-UUT). We investigated the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…There are only a few published reports of the expression of these genes in UTUC. Nakanishi et al [24] showed, in 125 cases of UTUC, no relationship between HTERT and clinicopathological findings, using in situ hybridization. Jeong et al [25] reported, from 112 patients, that BIRC5 expression assessed by immunohistochemistry was a poor prognostic factor for survival in patients with UTUC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few published reports of the expression of these genes in UTUC. Nakanishi et al [24] showed, in 125 cases of UTUC, no relationship between HTERT and clinicopathological findings, using in situ hybridization. Jeong et al [25] reported, from 112 patients, that BIRC5 expression assessed by immunohistochemistry was a poor prognostic factor for survival in patients with UTUC.…”
Section: Discussionmentioning
confidence: 99%
“…Nakanishi et al. [24] showed, in 125 cases of UTUC, no relationship between HTERT and clinicopathological findings, using in situ hybridization. Jeong et al.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one previous study has investigated hTERT and PCNA expression in malignancy, that of Nakanishi et al who also found no relationship between the two in urothelial cancers using in situ hybridisation and immunohistochemistry[27]. The correlation between PCNA and telomerase activity has been investigated in gastric carcinoma [28] and cervical intraepithelial neoplasia [29], and again no relationship found.…”
Section: Discussionmentioning
confidence: 99%
“…UTUC is less frequent and comprises approximately 5% of urothelial carcinomas [23]. Like other human malignancies, most RCCs and UTUCs exhibit telomerase activation [24,25], which suggests a possibility that TERT promoter mutations occur in these tumors. However, Vinagre et al analyzed 26 RCC tumors including 12 ccRCCs, 4 chRCCs and 10 PRCCs, and did not find any mutation-positive cases [8].…”
Section: Introductionmentioning
confidence: 99%